Pengaruh Profitabilitas, Kebijakan Utang, Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Perusahaan Sektor Keuangan di Bursa Efek Indonesia Tahun 2019-2021 - Rudiyanto Hartono, Dwiki; Susanti, Santi; Fauzi, Achmad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of Profitability, Debt Policy, and Investment Decisions on Firm Value. The data collection method used is a quantitative method. The population in this study is the financial sector listed on the Indonesia Stock Exchange (IDX) for 2019-2021 with a total of 105 companies. The data was obtained by collecting the company's annual financial report data on the Indonesia Stock Exchange (IDX) website. This study used a purposive sampling technique and the sample used was 71 companies by reducing the companies that fit the criteria. The results showed that profitability and investment decisions have a positive effect on firm value. Meanwhile, debt policy has no effect on firm value.